Pengaruh Person Organization Fit Dan Person Job Fit Terhadap Job Satisfaction Pegawai BPR Duta Artha Sejahtera - Qonakis Iskandar, Litaniar; Suratman, Maman (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study was conducted to describe the influence of Person-Organization Fit and Person-Job Fit on Job Satisfaction among employees of BPR Duta Artha Sejahtera. The research method used was quantitative, with a sample of 36 employees selected from the entire population. Data collection was carried out through literature review, observation, interviews, and questionnaires, which served as guidelines for conducting interviews. The data analysis technique employed was multiple linear regression analysis using SPSS version 24. The results of the study indicate that both Person-Organization Fit and Person-Job Fit have a positive and significant effect on Job Satisfaction, both partially and simultaneously